2016
DOI: 10.4103/1463-1741.181999
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in the Royal Norwegian Navy: A longitudinal study

Abstract: The aims of this longitudinal study were to investigate a significant threshold shift (STS) among personnel working on board the Royal Norwegian Navy's (RNoN) vessels between 2012 and 2014 and to identify possible determinants of STS. Hearing thresholds were measured by pure tone audiometry in two consecutive examinations (n = 226). STS was defined as an average change in hearing thresholds ≥ + 10 dB at 2,000 Hz, 3,000 Hz, and 4,000 Hz in either ear. Determinants of STS were assessed through a questionnaire. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…[14] Similarly, a recent study found a significant shift (23.0%) in the hearing threshold among personnel onboard the Royal Norwegian Navy's vessels between 2012 and 2014. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[14] Similarly, a recent study found a significant shift (23.0%) in the hearing threshold among personnel onboard the Royal Norwegian Navy's vessels between 2012 and 2014. [15]…”
Section: Discussionmentioning
confidence: 99%
“…In the Royal Norwegian Navy, it was found that the prevalence and incidence of hearing loss were 35% and 23%, respectively. 2 In Thailand, in the Royal Thai Fleet, in a study, there were 46.5% of ship officers exposed to loud noises, 3 and 31.25% had hearing loss. 4 The impact of occupational noise-induced hearing loss (ONIHL) is a public health burden that affects individuals, the workplace, and the economy.…”
Section: Pacific Rim Int J Nurs Res • October-december 2023mentioning
confidence: 98%
“…No Brasil, mesmo com a subnotificação desse agravo, sabe-se que a perda auditiva induzida por níveis de pressão sonora elevadas ainda é frequente 3 . Sendo assim, a perda auditiva e suas consequências são importantes problemas de saúde pública em nível mundial 4,5 .…”
Section: Introductionunclassified